NUMERICAL AXIAL IMPACT SIMULATION OF FOAM-FILLED CRASH-BOX: EVALUATION OF ALUMINUM FOAM MATERIAL MODEL - Farditya Akmal A, Muhammad
The development in transportation technology has to be followed by its safety environment. In a crash events, crashworthy structure is essential to reduce passengers’ injury risk through a good energy management. One of the common energy absorber is crash-box. A hollow thin-walled structure is commonly used but recent studies show the excellent characteristic of aluminum foam as a crashbox filler. The studies of numerical model for aluminum foam are also increasing to fit the experimental result. In this thesis, four configurations of crash-boxes; single-walled, double-walled, single-walled foam-filled, and double-walled foam filled were analyzed numerically where each crash-box with fixed bottom end was impacted by a rigid impactor with prescribed mass and velocity. The geometry of each crash-box’s wall was modeled using shell element and its material using MAT24. Two models of aluminum foam were developed, i.e. solid geometry with Deshpande-Fleck foam material model (MAT154), and cruciform geometry with piecewise linear plasticity material model (MAT24). The results were validated by comparing them with existing experimental data and numerical data from simulations with foam modeled as solid geometry with crushable foam material (MAT63). The study showed that simulation results using the crash-box with foam modeled as solid-MAT154 had differences of 10.8%, 9.6%, and 8.9% on the values of respectively peak force, mean crushing force, and displacement, which were higher compared to those obtained using the solid-MAT63 (2.4%, 6.08%, 4.59%) but smaller compared to those of cruciform-MAT24 (6.2%, 45.8%, 73.52%). The deformation modes obtained from model with MAT154 was also closer than those of the experiments. The cruciform-MAT24, however, provided more realistic information on how the foam and crash-box walls interact to each other.